(untitled) (Journal of the College of Basic Education, 2023)
This research is concerned with the structure of the text. For each text of a structure determined by its own literary genre, the upper structure consists of multiple blocks of blocks, the grand buildings. These large structures consist of a series of aggregate sequences linked in a structural way Or indirectly referred to as the smaller structures of text, the structure is a cornerstone of the coherence of a text and a sign of its interconnection